Effect of Heating Coarse Extract of Brown Macroalgae (Padina australis) from Tial Waters, Salahutu District, Central Maluku Regency on Antioxidant Activity - Hasanela, Nurani; Souhoka, Fensia Analda (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2022)
Physical and chemical factors influence antioxidant activity. One of the physical factors that can affect antioxidant activity is heat. This study aims to determine the phytochemical content and the effect of heating the crude extract of marine macroalgae Padina australis on antioxidant activity. The research method used, namely maceration using methanol as a solvent to obtain a crude extract, then evaporation of the solvent at a temperature of 45 °C. Furthermore, phytochemical tests were carried out, characterization using TLC and UV-Vis spectrophotometer, and determination of free radical scavenging activity of DPPH. The results of the phytochemical test showed that the crude extract of Padina australis was positive for bioactive compounds, namely saponins, alkaloids, terpenoids, steroids, and flavonoids. Characterization by TLC and UV-Vis spectrophotometer showed the presence of secondary metabolites, namely chlorophyll a and carotenoids. The use of temperature in the solvent evaporation process affects the stability of bioactive compounds and secondary metabolites. The results of the antioxidant activity test (IC50) of the crude extract of Padina australis against DPPH obtained 163 ppm, so it is classified as an antioxidant in the medium category.